2022
DOI: 10.1002/bse.3213
|View full text |Cite
|
Sign up to set email alerts
|

Green innovation and enterprise reputation value

Abstract: Using the data of Chinese listed enterprises in 2007-2020, we investigate the relationship between green innovation (GI) and enterprise reputation via OLS regression, IV-Lasso, and random forest. Findings show that GI can improve enterprise reputation, and it has a significant positive lag effect. Additionally, we compare the different effects of green patent applications and approved green patents. A possible mechanism is that GI reduces the pollution emission of enterprises. GI also performs better in improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…The adoption of a sample of Chinese companies to achieve our research objectives is instrumental in drawing applicable conclusions that can provide policy inspiration to other emerging developing as well as developed countries. Moreover, as mentioned above, corporate green innovation developed rapidly in China in the last decade and received considerable attention from scholars (Chen, Hao, et al, 2022; Hao et al, 2022; Li et al, 2019), thereby ensuring the reliability and representativeness of our findings. Second, the Chinese stock market is the fastest‐growing and largest emerging market (Li & Li, 2022).…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…The adoption of a sample of Chinese companies to achieve our research objectives is instrumental in drawing applicable conclusions that can provide policy inspiration to other emerging developing as well as developed countries. Moreover, as mentioned above, corporate green innovation developed rapidly in China in the last decade and received considerable attention from scholars (Chen, Hao, et al, 2022; Hao et al, 2022; Li et al, 2019), thereby ensuring the reliability and representativeness of our findings. Second, the Chinese stock market is the fastest‐growing and largest emerging market (Li & Li, 2022).…”
Section: Introductionmentioning
confidence: 77%
“…Lin et al (2020) argued that firms' green innovation strategies can also reduce firm idiosyncratic risks. Moreover, green innovation also contributes to firms' reputation and brand value (Chen, Hao et al, 2022; Lin et al, 2021), which can help firms create a positive image in the market and improve their green core competitiveness (Chang, 2011; Chiou et al, 2011). Prior studies also showed that green innovation enables firms to obtain increased government support and credit loans to alleviate their financing constraints (Owen et al, 2018; Xing et al, 2021).…”
Section: Literature Review and Theoretical Developmentmentioning
confidence: 99%
See 3 more Smart Citations